Formulation and Optimization of Aceclofenac Loaded Nanosuspension (International Journal of Pharmacy & Integrated Health Sciences, 2021)
Background: The aceclofenac sodium is used as non-steroidal anti inflammatory drug (NSAID), administered through the oral route, causing numerous side effects like nausea, vomiting, dyspepsia, gastrointestinal bleeding and peptic ulcer. NSAIDs, promote the secretions of hydrochloric acid which cause severe damage to the walls of gastro intestinal tracts well as to the drug.